Determinación de la frecuencia folículos anovulatorios en yeguas criollas colombianas (2022)
According to its reproductive physiology, the mare is considered a polyestrous animal. seasonal, therefore, its estrous cycle will depend on the amount of exposure to light hours, this in order to trigger ovulation. Sometimes the reproductive tract presents some pathologies among which are anovulatory follicles, which are characterized by cause a persistent follicle causing reproductive failure and not allowing trigger ovulation